Bleeding Risk with Dual Antiplatelet Therapy and Gastrostomy Tube Placement: : A Systematic Review and Network Meta-Analysis - Gangwani, Manesh K. (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.